Constitutionalism and transnational governance failures - Petersmann, Ernst-Ulrich; Steinbach, Armin (World Trade Institute advanced studies ;, 2024)
"This book explores strategies for limiting transnational market failures, governance failures, and constitutional failures impeding protection of the universally agreed sustainable development goals like climate change mitigation and access to justice and transnational rule-of-law. Can multilevel democratic and judicial protection of fundamental rights and public goods across frontiers be extended through plurilateral agreements? Can transnational economic and environmental constitutionalism be reconciled with 'constitutional pluralism' and with democratic constitutionalism depending on individual and democratic consent of free and equal citizens? Will judicial challenges (e.g. of European Union carbon border adjustment measures) and countermeasures lead to further disruption of United Nations and World Trade Organization law?" --